Puma predation on Magellanic penguins: An unexpected terrestrial-marine linkage in Patagonia - Serota, Mitchell W. (2023)
The global loss of top predators has led to widespread changes in food webs. In Patagonia, it is hypothesized that local extirpations of terrestrial predators, including the puma (Puma concolor), has led to the expansion of Magellanic penguin (Spheniscus magellanicus) colonies across the Atlantic coast of Argentina. Interestingly, more recent wildlife conservation efforts in the region have led to an unexpected trophic link between pumas and penguins. Here, we used a camera trap array to assess this novel predator-prey relationship between pumas and penguins in Monte Le´on National Park (MLNP) over a three-month period. Pumas were detected 12.5 times more than any other mammalian predator and were detected on 95% of the days during our study period. We alsoobserved 28 individual events of pumas preying upon penguins. Our work demonstrates a strong linkage between the marine and terrestrial ecosystem at MLNP. Puma predation of penguins may have widespread ecological implications including effects on puma and penguin abundance, changes in puma social behavior, and interspecific competition among other prey items and carnivores in the park. We propose hypotheses and questions to investigate these potential outcomes.